Peningkatan Hasil Belajar Siswa dengan Model Course Review Horay Metode Problem Posing pada Materi Larutan Elektrolit dan Nonelektrolit di Kelas X MIPA SMA Negeri 1 Tomohon - Maria Pangkey; Meytij Rampe; Ardi Kapahang (Chemistry Department, Universitas Negeri Manado, 2022)
This study aims to improve student learning outcomes on electrolyte and nonelectrolyte solutions through the application of the course review horay cooperative learning model with the problem posing method. The course review horay model of the problem posing method is a model that can enable students to search and find answers to a problem and the learning process also becomes more interesting. This research is classroom action research (CAR) which is conducted in 2 cycles, where each cycle consists of planning, action, observation, and reflection stages. The research subjects were all students of class X MIPA 1 at SMA Negeri 1 Tomohon, which consisted of 28 students consisting of 18 female students and 10 male students. Data collection techniques were carried out through observation and tests. Cycle I, the percentage of students' mastery classically is 78.57%. Cycle II the percentage of classical completeness to 100%. There was an increase in individual learning outcomes, with 22 students who finished studying in the first cycle to 28 students who finished learning in the second cycle. The results showed that the course review horay learning model with the problem posing method on electrolyte and nonelectrolyte solutions improved student learning outcomes.